Interaction of gangue minerals with malachite and implications for the sulfidization flotation of malachite - Liu, Cheng; Zhu, Guangli; Song, Shaoxian; Li, Hongqiang (Colloids and surfaces. A, Physicochemical and engineering aspects, 2018)
The interation of quartz-malachite and calcite-malachite are present by zeta potential distribution. [Display omitted] The role of gangue minerals including quartz and calcite slimes in the sulfidization flotation of malachite was investigated by micro-flotation tests, sedimentation analysis, zeta potential distribution measurements and DLVO calculations. The micro-flotation results showed that calcite slime depressed malachite flotation at pH 9.5 while quartz slime does not appear to influence malachite flotation. Sedimentation tests showed that hetero-coagulation occurred in both of malachite-calcite and malachite-quartz systems. The zeta potential distribution of individual minerals and mixed minerals measurements were used to describe the observed depression of sulfidization flotation of malachite by calcite but not quartz slime addition. DLVO calculation can be explained the hetero-coagulation in malachite-calcite system but not in malachite-quartz system, this may be attributed to the dissolved species of malachite adsorbed on quartz surface in malachite-quartz system.